2019
DOI: 10.1002/cti2.1045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum interleukin(IL)‐1α, IL‐1β and IL‐18 in patients with systemic sclerosis

Abstract: Objectives Systemic sclerosis ( SS c) is an autoimmune disease characterised by fibrosis, vascular dysfunction and immune dysregulation. The pathogenesis of SS c remains poorly understood, although studies have indicated a role for the innate immune response. Methods Here, we measured serum interleukin ( IL )‐1α, IL ‐1β and IL ‐18 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For example, some studies have indicated a significant increase in the content of caspase-1 in the skin tissue of SSc patients [160], while the level of caspase-1 in peripheral blood is significantly decreased [161]. In addition, Emily Lin et al found a lack of significant alteration in the level of IL-1β in the serum of SSc patients [162], while Y.-J. Zhanget al showed a significant increase [163].…”
Section: Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies have indicated a significant increase in the content of caspase-1 in the skin tissue of SSc patients [160], while the level of caspase-1 in peripheral blood is significantly decreased [161]. In addition, Emily Lin et al found a lack of significant alteration in the level of IL-1β in the serum of SSc patients [162], while Y.-J. Zhanget al showed a significant increase [163].…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…Furthermore, the levels of NLRP3-related cytokines in SSc patients are closely correlated with certain clinical indicators. High levels of IL-18 in the serum indicate poor pulmonary function in patients, while high levels of IL-1β in skin tissue indicate severe skin fibrosis [160] and relatively better lung function [162]. However, there are also studies that refute the clinical predictive value of IL-1β levels in the serum [163].…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…This can be seen from a study they conducted on model mice with IL-18 deficiency, which experienced more severe fibrosis than wild-type mice. Another study by Kim et al showed that IL-18 downregulation occurs in human dermal fibroblasts which also indicates an anti-fibrotic effect of IL-18 on SSc, so that the actual role of IL-18 as a pro-fibrotic or anti-fibrotic still requires further research [41,42].…”
Section: Interleukin-18 (Il-18)mentioning
confidence: 99%
“…In addition, the serum level of IL-1α in SSc is controversial. Lin et al reported that SSc patients with high serum IL-1α concentrations were more likely to have digital ulcers (24). These data emphasize the need for further research to determine the role of IL-1α in SSc pathogenesis, particularly in obliterative vasculopathy.…”
Section: The Expression and Function Of Il-1 Family Cytokines In Sscmentioning
confidence: 99%